Plasma metabolomics and red blood cell fatty acid profiles in adolescent mental health - Piironen, Aino-Kaisa; Afonin, Alexey M.; Zarei, Iman; Koistinen, Ville; Lehtonen, Marko; Hämäläinen, Venla; Sala-Vila, Aleix; Lázaro, Iolanda; Julvez, Jordi; van Kamp, Irene; Kanninen, Katja M. (Elsevier, 2026)
Rising mental health challenges among adolescents are a global priority, yet tools to identify at-risk individuals remain limited. The development of objective tools, such as plasma biomarkers, could enhance the implementation of early preventive strategies for individuals at increased risk. We explored plasma metabolites associated with overall psychosocial difficulties in 197 adolescents aged 11-16 from the WALNUTS study. Psychosocial difficulties were assessed using self-reported Strengths and Difficulties Questionnaire (SDQ) scores. Plasma metabolomics data were generated by untargeted liquid chromatography high-resolution mass spectrometry using cross-sectional plasma samples. Linear regression modelling was performed to identify associations between plasma metabolites and the total SDQ score. Logistic regression and Precision-Recall curves were used to evaluate the classification performance of candidate metabolites in distinguishing the SDQ groups (low: 0–14; raised: 15–25). Additionally, pre-existing red blood cell fatty acid profile data were analysed to detect differences between the low and the raised SDQ score groups. Three metabolites: isoleucine, pregnenolone sulfate, and lysophosphatidylcholine 20:1, were significantly associated with the SDQ score, and are involved in energy metabolism, neuronal functions and phospholipid-related signalling. In addition, a trend towards lower proportions of red blood cell n-3 polyunsaturated fatty acids was observed in individuals with the raised SDQ score. This exploratory study observed associations between three plasma markers and the total SDQ score, reflecting psychosocial, behavioural, and emotional difficulties in adolescents.